Accelerative and decelerative effects of hedonic valence and emotional arousal during visual scene processing. Issue 7 (July 2013) - Ihssen, Niklas; Keil, Andreas
Perceptual processing of natural scene pictures is enhanced when the scene conveys emotional content. Such "motivated attention" to pleasant and unpleasant pictures has been shown to improve identification accuracy in non-speeded behavioural tasks. An open question is whether emotional content also modulates the speed of visual scene processing. In the present studies we show that unpleasant content reliably slowed two-choice categorization of pictures, irrespective of physical image properties, perceptual complexity, and categorization instructions. Conversely, pleasant content did not slow or even accelerated choice reactions, relative to neutral scenes. As indicated by lateralized readiness potentials, these effects occurred at cognitive processing rather than motor preparation/execution stages. Specifically, analysis of event-related potentials showed a prolongation of early scene discrimination for stimuli perceived as emotionally arousing, regardless of valence, and reflected in delayed peaks of the N1 component. In contrast, the timing of other processing steps, reflected in the P2 and late positive potential components and presumably related to post-discriminatory processes such as stimulus–response mapping, appeared to be determined by hedonic valence, with more pleasant scenes eliciting faster processing. Consistent with this model, varying arousal (low/high) within the emotional categories mediated the effects of valence on choice reaction speed. Functionally, arousal may prolong stimulus analysis in order to prevent erroneous and potentially harmful decisions. Pleasantness may act as a safety signal allowing rapid initiation of overt responses.